Biological Spectrum of Garhwal Siwalik - Rajwar, G. S.; Gupta, Subodh K. (Indian Forester, 1984)
The biological spectrum of Garhwal Siwalik has been studied in relation to the environment. Life forms in the order of importance recorded were therophytes (62.8%), phanerophytes (26.8%), chamaephytes (5.7%), geophytes (4.5%) and hemlcryptophytes (0.2%). The vegetation appears to be predominating by phanerophytes except the river banks and other disturbed areas where therophytes are dominating.